2014
DOI: 10.1016/j.ijid.2014.03.1390
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a quadrivalent meningococcal polysaccharide CRM conjugate vaccine in infants and toddlers

Abstract: MenACWY-CRM vaccination regimens in infants and toddlers were immunogenic and well tolerated. No clinically meaningful effects of concomitant administration with routine infant and toddler vaccines were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 10 publications
2
28
0
5
Order By: Relevance
“…Geometric mean titers were also modest across serogroups. Similarly, by 6 months after a 3-dose series of MenACWY-CRM given at 2, 4 and 6 months of age in infants, 9,10 antibody titers declined to different degrees across serogroups, with more than half of the infants retaining antibody titers 8 against serogroups C, W and Y at 6 months after vaccination (Fig. 3).…”
Section: Persistence After Multi-dose Vaccination Series In Infants Amentioning
confidence: 85%
See 2 more Smart Citations
“…Geometric mean titers were also modest across serogroups. Similarly, by 6 months after a 3-dose series of MenACWY-CRM given at 2, 4 and 6 months of age in infants, 9,10 antibody titers declined to different degrees across serogroups, with more than half of the infants retaining antibody titers 8 against serogroups C, W and Y at 6 months after vaccination (Fig. 3).…”
Section: Persistence After Multi-dose Vaccination Series In Infants Amentioning
confidence: 85%
“…[7][8][9][10] This review appraises data from 7 phase 3 and phase 4 studies, with the objective of providing an overview of antibody persistence following primary vaccination with MenACWY-CRM vaccine, and responses to booster doses of the vaccine. 9,10,[11][12][13][14][15][16][17][18][19] Only data pertaining to the recommended dose schedules of MenACWY-CRM in each age group is assessed here : a single dose in children 2-10 y of age, adolescents and adults; 4 doses at 2, 4, 6 and 12 months of age in infants; and 2 doses given to unvaccinated children between 7-23 months of age. All the studies included in this review were conducted in accordance with good clinical practice and International Conference on Harmonisation of Techniques for Requirements for Registration of Pharmaceuticals for Human Use guidelines, and were approved by Institutional Review Boards (IRBs) or Ethics Committees (ECs) in each country, as appropriate, prior to start of the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining four abstracts were considered not relevant with respect to objectives or did not report data on co-administration of RV and meningococcal vaccines. Eleven studies provided information on the safety profile of co-administration of RV vaccines and meningococcal vaccines [20][21][22][23][24][25][26][27][28][29][30] and five studies reported data on immunogenicity. 21,22,24,29,31 No studies presented data on vaccine efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that conjugate vaccines in children less than 2 years of age are highly immunogenic and induce substantial Bcell memory in young infants, which make them more efficacious than polysaccharide vaccines [16]. Studies have shown that a quadrivalent meningococcal conjugate vaccine Men ACWY-CRM used in infants and toddlers was immunogenic and well tolerated [17,18]. The UK experience with the conjugate meningococcal serogroup C vaccine resulted in decreased hospital admissions with meningococcal diseases in children from 34.5/100,000 in 1999 to 12.4/100,000 in 2011 [19].…”
Section: Discussionmentioning
confidence: 99%